Financial Comparative Analysis of State Public Universities of Punjab - Kaur, Sarbjeet; Singh, Gurcharan (International Journal of Economics and Financial Issues, 2020)
Finance is the strategic intent to boost the development and growth of all industries. Presently, Indian higher education has attained an impressive growth rate, and finance is playing a vital role in its continuous development and attaining a competitive edge. Therefore, the present study aims to analyze the financial performance of the Indian public universities located within Punjab. The data of universities’ financial performance between 2003 and 2019 were taken into consideration. The Welch and post-hoc tests were employed to answer the research questions. The study found no significant difference in the income level of the universities but the results confirmed a significant difference in expenditure level. The findings of the study may draw the attention of academicians, and policymakers to build a balance between income and expenditure. Keywords: Higher education, Financial Performance, Reports, Budget. JEL Classifications: G2, H61, I23 DOI: https://doi.org/10.32479/ijefi.10458